PENGARUH INFLUENCER TERHADAP BRAND AWARENESS DI HOTEL WYNDHAM CASABLANCA JAKARTA - Ghazzani, Athifa; Masnar, Asriadi; Dwilanisusantya, Carissa (Jurnal Perhotelan dan Pariwisata, 2024)
The background of the research is based on the growing trend of digital marketing, where Influencers are considered effective in increasing consumer interest and Brand awareness, particularly among Millennials and Gen Z. This research uses a quantitative approach with survey techniques through questionnaires distributed to 100 respondents. The data were analyzed using t-tests and correlation analysis with the assistance of SPSS version 30. The results show that the t-value of 8.366 is greater than the t-table value of 1.984 at a 5% significance level, indicating a significant influence between Influencers and Brand awareness. Therefore, it can be concluded that Influencers play an important role in strengthening the Brand awareness of Hotel Wyndham Casablanca Jakarta through appealing visual content and personal credibility that effectively influence consumer perceptions. Keywords: Influencer; Brand awareness; Hotel; Social Media; Digital Marketing